An Assymetric Evaluation of Oil Price- Inflation Nexus: Evidence from Nigeria - Alimi, Ahmed S.; Olaniran, Oladotun D.; Ayuba, Timothy (Energy Economics Letters, 2020)
This paper investigates the asymmetric oil price-inflation nexus in Nigeria covering the period of 2009Q1 and 2018Q4. We adopt the Nonlinear Autoregressive Distributed Lags (NARDL) model approach. The result of the study indicates that there exists a nonlinear long run connection between international oil price and inflation in Nigeria which suggests that fluctuations in oil price influence domestic inflation in Nigeria asymmetrically. Further, the result of the study indicates that in the long run, both increase and decrease in global oil price exerts a negative effect on inflation, that is, rise and fall in global oil price will lead to decline in inflation. However, in the short run, increase in global oil price exerts a positive influence on inflation which implies that positive oil price shock is inflationary. The study therefore recommends that government need to source for alternative energy in order to minimize the influence of international oil price shocks on domestic price level.